Representações mobilizadas nas turmas de 1º ano do Colégio de Aplicação da Universidade Federal de Sergipe no ensino de função afim e quadrática - Meneses, Leonel Ricardo Machado (2014)
The object of mathematical study titled function is present in several everyday situations, being used by several areas of knowledge. In this way, the acquisition of its concept becomes fundamental for the development of the individual’s cognitive that is in contact with the mathematics in and out of school. Thus, with the work presented here, it was aimed to analyze the mathematical representations mobilized by the students of the 1st year of high school from Colégio de Aplicação of the Universidade Federal de Sergipe (CODAP/UFS) during the teaching of affine and quadratic function. For this purpose, this study was based on Duval's theory of the registers of semiotic representation (2003, 2009, 2011) as well as the guidelines of the Parâmetros Curriculares Nacionais (BRASIL, 1999, 2002, 2006). In addition to that, it was taken as source the textbook Matemática: Contexto & Aplicações (DANTE, 2010), adopted by the participant groups of the research, as well as photocopies of the four (4) participating students' notebooks and 51 (fifty-one) protocols from a sequence of activities composed of 04 (four) problems that were developed with the students themselves. Among the obtained results, it was pointed out that, as in the 499 (four hundred and ninety-nine) activities categorized in the textbook as in the 108 (one hundred and eight) categorized in the students' notebooks, it was required the semiotic transformation of conversion in the majority of them, this is: 446 (four hundred and forty-six) activities, 89.38%, and 83 (eighty-three), 76.85%, respectively. In addition, the activities proposed by the textbook and those contained in the students' notebooks did not prioritize the back and forth feature of the registers among the conversions, disrupting, according to DUVAL (2003, 2009, 2011), the process of acquiring the concept of function. Moreover, in both research instruments it was noticed that, in conversions in which the graphic records were necessary, they were practically not presented, causing important losses in the process of acquisition of the concept of function. Therefore, among the main results obtained with this sequence of activities, it was highlighted that the vast majority of the individuals used in the research used algorithmization processes to perform most conversions. Finally, many of the students used case-by-case analysis and demonstrated that they were not able to identify and use the relevant visual variables to perform the conversions.